Andalusia, the Trans-European Transport Network and public transport and territorial cohesion policies. The Malaga-Seville territorial axis - Nuevo-López, Abraham; Mérida-Rodríguez, Matías Francisco (Revista de Estudios Andaluces, 2022)
The aim of this research is to analyse the evolution of the Trans-European Transport Network (TEN-T) on the Malaga-Seville territorial axis, as well as on public transport policies and on the aspect of territorial cohesion, in particular as regards the rail network. The qualitative methodology used in the article is based on systematic and documentary literature review. The results of the work show that the TEN-T play a decisive role in the objective of territorial cohesion in Andalusia, although there is still insufficient development of these networks and a certain political incapacity persists. It is concluded that the TEN-T have been particularly important for the railway infrastructure of Andalusia.